The Implementation of Authentic Assessment to Evaluate the Students’ Speaking Skill - Junaedi, Sony (Journal of English Language Teaching and Islamic Integration (JELTII), 2019)
The study mainly aims at describing the implementation of authentic assessment to evaluate the students’ speaking skill in the classroom that conducted by lecturer. The objectives of this study were: to describe the authentic assessment implementation, lecturers’ achievement, their problems, causes of their problems. The research design was case study. Two English lecturers were chosen as the subjects. The fourteen class observations, questionnaire and interview were conducted to collect the data. The data were analyzed by using Miles and Huberman’ model of analysis. The findings showed that basically, two English lecturers have just implemented the authentic assessment but they have not been able to implement it completely, properly, and smoothly in speaking class yet. Some suggestions can be given in the study. They should prepare the time allotment properly before preparing, implementing, and scoring students’ skill, look for many references, join workshop or conference that  relating to the authentic assessment in order to understand the ways to design and implement the authentic assessment, score students’ skill and practice them correctly.